2019
DOI: 10.1371/journal.pone.0212532
|View full text |Cite
|
Sign up to set email alerts
|

Aerial-trained deep learning networks for surveying cetaceans from satellite imagery

Abstract: Most cetacean species are wide-ranging and highly mobile, creating significant challenges for researchers by limiting the scope of data that can be collected and leaving large areas un-surveyed. Aerial surveys have proven an effective way to locate and study cetacean movements but are costly and limited in spatial extent. Here we present a semi-automated pipeline for whale detection from very high-resolution (sub-meter) satellite imagery that makes use of a convolutional neural network (CNN). We trained ResNet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 44 publications
(36 reference statements)
0
59
0
Order By: Relevance
“…Despite the promise that VHR satellites hold, currently images must be manually analysed by experts, which hinders their application in practice. While researchers would benefit from surveying large areas (e.g., searching for whales in open ocean [4]), manually scanning through enormous volumes of imagery becomes a near impossible task, particularly if surveys are to be repeated regularly [11]. Due to this most research has been limited to comparatively small scale studies over a few square kilometers [2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promise that VHR satellites hold, currently images must be manually analysed by experts, which hinders their application in practice. While researchers would benefit from surveying large areas (e.g., searching for whales in open ocean [4]), manually scanning through enormous volumes of imagery becomes a near impossible task, particularly if surveys are to be repeated regularly [11]. Due to this most research has been limited to comparatively small scale studies over a few square kilometers [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, trained algorithms with known, quantifiable uncertainties may provide a more analytically uniform means of scanning, identifying and classifying FOIs. Studies 55,56 have shown remarkable progress in this field over recent years,however ongoing development and testing is still required to hone these methods in order to assess their accuracy when compared to visual observations in challenging conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have explored both manual [ 10 , 11 , 12 , 27 ] and automated [ 28 , 29 ] methods of analysis ( Figure 1 ). Manually counting whales in satellite images is currently the most accurate method, although the most time-consuming, as it can require approximately 3 h and 20 min to scan 100 km 2 [ 12 ], and be erroneous due to observer bias [ 30 ].…”
Section: Considerations and Challenges Inherent To Satellite Imagementioning
confidence: 99%
“…Given the current limits on the available data of labelled satellite images of whales and similarly labelled images of confounding features within satellite imagery (e.g., rocks, boats, and white caps), required to create such a training dataset, aerial imagery can be used as a substitute for satellite imagery, to get the process underway. These aerial images should be down-sampled to the spatial resolution of VHR satellite imagery [ 28 ]. Alternatively, freely available photo archives of aerial and satellite imagery, can be accessed from sources such as Google Earth [ 29 ].…”
Section: Considerations and Challenges Inherent To Satellite Imagementioning
confidence: 99%